The influence of social media marketing and e-word of mouth in building purchase intention of kopibanaxfallenskitchen mediated by brand image. - Afdhal Mulya Putta; Susi Evanita (Marketing Management Studies, 2021)
The purpose of this study is to analyze the extent to which the influence of Social Media Marketing and e-word of mouth in building purchase intention mediated brand image. A The point of this study is: (1) This a direct and up to and positive effect amongsocial media and purchase intention on Kopibanaxfallenskitchen. (2) There is a direct and significant and positive influence between Electronic Word of Mouth and purchase intention on the Kopibanaxfallenskitchen object. (3) This a direct andup to and positive effect amongsocial media and brand image on Kopibanaxfallenskitchen. (4) There is a direct and significant and positive influence between electronic wordof mouth and brand image in Kopibanaxfallenskitchen. (5) there is a direct and significant and positive effect between brand image and purchase intention on Kopibanaxfallenskitchen. This means that Kopibanaxfallenskitchen consumers feel that the Kopibanaxfallenskitchen brand image can influence and increase their desire to buy the culinary. (6) There is an indirect and significant and positive influence between social media and purchase intention through brand image on Kopibanaxfallenskitchen.